PENGARUH KENAIKAN HARGA BBM TERHADAP HARGA TARIF TRANSPORTASI UMUM DI KOTA PADANG - Ulia Safitri; Dina Friska; Uswatun Hasanah; Ismi Khoiro; Aqshal Noer Salim; Abdan Syakur (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Fuel Oil is a commodity that plays a vital role in all economic activities. Fuel oil (BBM) is energy that needs to be subsidized because the price of fuel is heavily influenced by external factors, namely the price of crude oil on the world market. Fuel subsidies from the government distributed by Pertamina are still limited to the types of kerosene, diesel and premium as the energy consumed by the public. The impact of the increase in world oil prices which resulted in the government reducing subsidies for domestic fuel affected the fares of public transportation, including public transportation in cities. In-town public transportation is a mode of transportation that connects one area to another in the city. Research on the amount of fares for inner-city transportation, especially with fluctuations in fuel price increases, needs to be examined to see the relationship between the percentage increase in fuel prices and the increase in public transport fares in the city. In this research, the route under review is the city center route – Padang.